Pengembangan Aplikasi Mobile Learning Konstruksi Jalan dan Jembatan Untuk Optimalisasi Pembelajaran SMK Jurusan Bangunan Kota Surakarta - Kusuma, Fajar Indra; Subiyantari, Ansheila Rusyda; Dian, Imam Fahmi; Fatima, Izma (Akademi Komunitas Negeri Aceh Barat, 2025)
The integration of technology in education, particularly in Vocational High Schools (SMK), is increasingly necessary to support interactive and digital-based learning. This study aims to develop a mobile-based learning media application for the subject of road and bridge construction for students in the building engineering department of SMK. Based on preliminary observations and data, 86% of the 96 respondents stated that conventional teaching methods remain ineffective, and 96% expressed the need for more interactive media. This research uses the Research and Development (RD) method with the Alessi Trollip model, consisting of three stages: (1) Planning (needs analysis of students and teachers), (2) Design (development of user interface, curriculum content, and simulation features), and (3) Development (program implementation to produce a product ready for testing). Alpha testing involving media experts, subject matter experts, and practitioners yielded a rating of